P337 Switching from originator infliximab to CT-P13: single-centre experience from the UK. (25th January 2019) - Bhandare, A P; Crooks, B; Nigam, G B; Limdi, J K
Abstract: Background: The infliximab biosimilar (CT-P13) received market authorisation for inflammatory bowel disease in late 2016 with the aim of reducing cost and increasing access to therapy. The prospect of 'switching' patients from originator to CT-P13 has concerned clinicians. #8232;We present an experience of 'switching' from originator infliximab (IFX-O) to CT-P13 and present efficacy, safety, and immunogenicity data from our cohort. Methods: We performed a retrospective review of patients switched from IFX-O to CT-P13. Disease demographics, clinical course and outcomes were analysed from electronic case records at a median of 8 months and at last follow-up at 13 months. Results: Ninety-six patients (35 females) were 'switched' from IFX-O to CT-P13. Of these 44 had Ulcerative colitis (UC) and 52 had Crohn's disease (CD) with a mean age at diagnosis of 34.7 years (median = 33, IQR = 24.5). Montreal phenotype for UC was E1 = 1, E2 = 16, E3 = 27 and for CD (L1 = 10, L2 = 12, L3 = 29, L4 = 1) and (B1 = 27, #8232;B2 = 14, B3 = 11), 9 patients had perianal disease. Mean duration of IFX-O treatment was 49. 8 months (median = 44, IQR = 52) and on CT-P13 11.5 months (median 13). At switch, 76 patients had a normal CRP (UC = 33, CD = 43), and in 15 patients it was elevated (UC = 10, CD = 5). At 8 months, 80 patients remained in biochemical remission (UC = 35, CD = 45 ) and in 14 patients (UC = 8, CD = 6 ) CRP increased. Seventy-two patients (UC = 34, CD = 38 ) were in clinical remission (pMayo < 2 and HBI < 5). Of 51 patients (UC = 21, CD = 30) undergoing endoscopic assessment, 31 achieved mucosal healing (UC = 13, CD = 18). At 13 months, 69 patients remained on CT-P13. Twenty-seven discontinued the drug due to immunogenicity ( n = 10), loss of response ( n = 5), surgery ( n = 5), remission ( n = 5), side effects ( n = 2 ), and 1 patient died of hospital acquired pneumonia. 39 out of 96 patients had therapeutic drug levels checked within 13 months of switch, of whom 27 had sub-therapeutic levels (below 4 μg/ml). Antibodies to Infliximab were seen in 15 of 39 patients (38.5%), of whom 8 were switched to an alternative biologic, 2 had dose escalation (10 mg/kg IFX), 4 patients stopped IFX with no other intervention, and 1 person continued treatment at same dose with low antibody titre of 6. Conclusions: Biosimilar IFX (CT-P13) was well tolerated. Clinical efficacy and loss of response rates with CT-P13 appears to be similar to IFX-O. This holds promise for a wider adoption of 'switching' to fulfil the purported aims of wider access to treatment at a lower cost.